2020
DOI: 10.3390/s20061627
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Visual Stimuli on Personal Thermal Comfort Perception in Real and Virtual Environments Using Machine Learning Approaches

Abstract: Personal Thermal Comfort models consider personal user feedback as a target value. The growing development of integrated “smart” devices following the concept of the Internet of Things and data-processing algorithms based on Machine Learning techniques allows developing promising frameworks to reach the best level of indoor thermal comfort closest to the real needs of users. The article investigates the potential of a new approach aiming at evaluating the effect of visual stimuli on personal thermal comfort pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…The FFNN-PSO-GSA model is trained using different predictor combinations to be compared against the results reported in the literature. The suggested model yields a classification accuracy ranging between 98.47-98.73% using one predictor (i.e., temperature), higher than the reported value of 67-87% by Salamone et al (2020) and substantially higher than 55-65% reported in Sembroiz et al (2019). As for the temperature and CO2 predictors, the proposed model has an accuracy 2020) and 69-89% in Sembroiz et al (2019).…”
Section: Co2mentioning
confidence: 74%
See 1 more Smart Citation
“…The FFNN-PSO-GSA model is trained using different predictor combinations to be compared against the results reported in the literature. The suggested model yields a classification accuracy ranging between 98.47-98.73% using one predictor (i.e., temperature), higher than the reported value of 67-87% by Salamone et al (2020) and substantially higher than 55-65% reported in Sembroiz et al (2019). As for the temperature and CO2 predictors, the proposed model has an accuracy 2020) and 69-89% in Sembroiz et al (2019).…”
Section: Co2mentioning
confidence: 74%
“…Meanwhile, its accuracy ranged between 69% and 89% for temperature and CO2 predictors. Salamone et al (2020) evaluated occupant thermal comfort in real and virtual scenarios by combining the application of the internet of things and machine learning. Different machine learning techniques were fed with users' biometric and feedback data about their thermal comfort along with the environmental parameters.…”
Section: Occupancy Detection Modelsmentioning
confidence: 99%
“…It is possible to replace the categorical label 22-User following the same approach, considering all environmental and biometric data. In this way, it is possible to verify the importance of individual features to identify the target feature, Users (Figure 9) thus highlighting the interconnection among environmental parameters and biometric data, as discussed in recent studies [54,55]. In the Section 3.2.2, two lists of biometric features are selected.…”
Section: Sensors 2019 19 X For Peer Review 12 Of 25mentioning
confidence: 97%
“…It was not possible to assess whether the test rooms are located inside a building or are entirely independent buildings for 10% of the 187 test rooms identified. According to the available information, only 7% of the facilities are independent buildings, external to any other building [34][35][36][37][38][39][40][41][42][43][44][45][46][47]. Five of these independent test rooms are located on a platform that allows the whole structure to rotate [34][35][36][37]41].…”
Section: Construction Detailsmentioning
confidence: 99%
“…4). Among the 14 experimental facilities built outside, only one does not have windows [46]. At the same time, five include an adjustable envelope to vary the window-to-wall ratio (WWR) [35,37,41,43,45], five have a WWR lower than 0.5 [38,39,42,44,47], and three have a WWR in between 0.6 and 0.8 [34,36,40].…”
Section: Construction Detailsmentioning
confidence: 99%